PENDEKATAN METODE INDEKS TUNGGAL DALAM ANALISIS PEMBENTUKAN PORTOFOLIO OPTIMAL DARI SAHAM-SAHAM LQ45 PADA PERIODE WAKTU YANG BERBEDA - Eti Eti (Jurnal Akuntansi Bisnis, 2017)
The are many share type which offer on capital market, therefore investors can chose the shares according to the risk preference. Generally, every investor assumed as averter risk. It means that investor want more advantage in every increasing of the risk level. Most problems faced by investor when conducting investment in capital market is how to estimate risk level. To minimize risk loss of investments, investor usually will diversify with forming portfolio. The question is which portfolios are selected by investor and how to choose it. For that purpose, it needs analysis that be able to be guidance in  buying share for maximize expected return as according to its risk levelKeywords : Shares, Risk level, Portfolio, Investor